2011
DOI: 10.2319/040811-251.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of physical vapor deposition coated beta titanium orthodontic archwires

Abstract: Objective: To determine in vitro the frictional properties, surface morphology, and load deflection rate with looped designs of two newly developed titanium aluminum nitride (TiAlN) and tungsten carbide/carbon (WC/C) physical vapor deposition (PVD) coated beta titanium orthodontic archwires coated with PVD. Materials and Methods: Frictional properties with Tidy's protocol, surface evaluation before and after friction testing with the help of scanning electron microscopy (ESEM), and load deflection rate with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…They concluded that Ag-Pt coatings provide good antimicrobial activity during active orthodontic treatment. Krishnan et al [66] coated beta titanium orthodontic archwires with titanium aluminum nitride (TiAlN) and tungsten carbide/carbon (WC/C) using PVD and evaluated frictional properties, surface morphology, and load deflection rate. They found that WC/C archwires demonstrated reduced frictional properties, better surface characteristics, and low load deflection rate compared with TiAlN and uncoated archwires.…”
Section: Physical Vapor Deposition (Pvd)mentioning
confidence: 99%
“…They concluded that Ag-Pt coatings provide good antimicrobial activity during active orthodontic treatment. Krishnan et al [66] coated beta titanium orthodontic archwires with titanium aluminum nitride (TiAlN) and tungsten carbide/carbon (WC/C) using PVD and evaluated frictional properties, surface morphology, and load deflection rate. They found that WC/C archwires demonstrated reduced frictional properties, better surface characteristics, and low load deflection rate compared with TiAlN and uncoated archwires.…”
Section: Physical Vapor Deposition (Pvd)mentioning
confidence: 99%
“…Optical profilometer findings in control group show that surface roughness of TMA is significantly higher than that of LF and HD, which is in concurrence with previous results. [61718] Because those studies had used different evaluation methods, quantitative comparison of the surface deterioration of our study with theirs was not possible. This is in contradiction to the findings of Kusy who concluded that the surface roughness cannot be drastically reduced by ion implantation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous findings. [917] The lower load deflection properties of the colored TMA wires might be due to the etching and heating process, while coating is performed over archwire blanks. [9] There were no significant differences between HD and LF.…”
Section: Discussionmentioning
confidence: 99%
“… 12 - 14 Research has accordingly targeted different approaches, including surface treatments and coatings to further reduce friction between the bracket and archwire. 18 - 21 …”
Section: Introductionmentioning
confidence: 99%
“… 26 Another coating technique, physical vapor deposition, was used to coat beta titanium orthodontic archwires with titanium aluminum nitride and tungsten carbide/carbon for the assessment of frictional properties, the surface morphology, and the load deflection rate. 18 Radio frequency (RF) magnetron sputtering is another technique used for coating orthodontic materials. This technique removes surface atoms from a solid cathode (target) by bombarding it with positive ions from an inert gas discharge; then, it deposits the surface atoms on the surface to form a thin film.…”
Section: Introductionmentioning
confidence: 99%